2014
DOI: 10.1039/c4ta00871e
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Ti surface roughness in the self-ordering of TiO2 nanotubes: a detailed study of the growth mechanism

Abstract: Highly ordered TiO2 nanotubes (NTs) were synthesized by electrochemical anodization of Ti foils. We investigated the effect of the Ti surface roughness (applying different pretreatments prior to the anodization) on the length, growth rate and degree of selforganization of the obtained NT arrays. The mechanisms related to the TiO2 NT formation and growth were correlated not only with the corresponding anodization curves but also with their appropriate derivatives (1 st order) and suitable integrated and/or obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 56 publications
2
63
0
Order By: Relevance
“…1 x 1 µm 2 topographic images of Ti surfaces were obtained for each sample and then analyzed in terms of surface roughness (Rq), defined as the root-mean-square value of the images pixel height. Additionally, the Ti surface after EP revealed a periodic dimple-pattern structure whenever VEP was no smaller than 10 V. This shallow ripple-like structure is an EP characteristic of metals [33,41] and can be used as a pre-pattern prior to the anodization to obtain highly ordered oxide nanostructures, as profusely shown in the case of Al [27,[33][34][35][36]40]. In fact, studies in Al foils demonstrated that, by combining adequate EP voltage and time, dimple-patterns from striped to hexagonal arrangements can be obtained [27,[33][34][35][36]40].…”
Section: Afm Imaging Analyses: Surface Topography and Roughness Charamentioning
confidence: 96%
See 4 more Smart Citations
“…1 x 1 µm 2 topographic images of Ti surfaces were obtained for each sample and then analyzed in terms of surface roughness (Rq), defined as the root-mean-square value of the images pixel height. Additionally, the Ti surface after EP revealed a periodic dimple-pattern structure whenever VEP was no smaller than 10 V. This shallow ripple-like structure is an EP characteristic of metals [33,41] and can be used as a pre-pattern prior to the anodization to obtain highly ordered oxide nanostructures, as profusely shown in the case of Al [27,[33][34][35][36]40]. In fact, studies in Al foils demonstrated that, by combining adequate EP voltage and time, dimple-patterns from striped to hexagonal arrangements can be obtained [27,[33][34][35][36]40].…”
Section: Afm Imaging Analyses: Surface Topography and Roughness Charamentioning
confidence: 96%
“…After applying the anodization potential (60 V), a continuous TiO2 layer is rapidly formed increasing the resistance (rapid j decrease). The following slight j-decrease marks the onset of NT nucleation, likely on the surface valley-type irregularities where the higher electric field enhances oxide dissolution and hole formation (dissolution promoted by F -ions in favourable spots of the TiO2 surface) [41]. Consequently, the TiO2 layer thickness starts to decrease, while the pores (tubes) formation accelerates.…”
Section: Anodization Curves 121 Typical Growth Mechanismmentioning
confidence: 99%
See 3 more Smart Citations